Effect of Age on Retention Ability of Chemistry Students Exposed to E-Learning Instruction in Inorganic Chemistry - Ikpe, Adakole (West African Journal of Open and Flexible Learning, 2015)
This study examined the effect of age on the retention ability of chemistry students exposed to e-Learning instruction in Inorganic Chemistry at the National Open University of Nigeria (NOUN). A total of 45 students formed the sample of the study from a population of 453 students. Purposive sampling technique was used for choosing the centre and sample used for the study. The study used the One Group Pretest, Posttest, Post-Posttest pre- experimental design. Participants were taught selected concepts in Inorganic Chemistry using the e-Learning instructional strategy for a period of eight weeks. An instrument, Chemistry Achievement Test (CAT) was used to collect data; its reliability coefficient was 0.78. A research question was answered and null hypothesis was tested, using the One Way Analysis of Variance (One Way ANOVA) at P< 0.05. The major finding from the study was that there was no significant difference in the retention ability of subjects of different age groups in the study. Based on the findings, it was concluded that retention ability of students taught using the e-Learning instructional strategy does not depend on age. It was recommended that NOUN, Distance Learning Institutes and institutions of higher learning should incorporate/adapt the instructional Strategy for the teaching of chemistry. Students and teachers should also be regularly trained and retrained on the usage of e-learning platforms.